MENELUSURI JEJAK PENGUNGSI VIETNAM DI PULAU GALANG TENTANG SEJARAH, KONFLIK, DAN KENANGAN KELAM - Angelica Tan; Chilly Robilah Putri; vanessa angelyn; Galih Athoriq Permana Harahap; Rullyan Syah Lubis (Puslitabmas Batam Tourism Polytecnic, 2025)
Galang Island, under the administration of Batam City, Riau Islands, plays an important role in humanitarian and geopolitical history as a Vietnamese refugee camp from 1979 to 1996. After the Vietnam War conflict ended in 1975, around 250,000 Vietnamese fled to Southeast Asian countries, including Indonesia. Galang Island was chosen as the location for a refugee camp managed by UNHCR and the Indonesian government, providing facilities such as hospitals, schools, and places of worship. Although safe from conflict, the refugees faced hardships, uncertainty, and psychological trauma. The island is now a historical monument, but there are still many dark stories that are spread and trigger confusion. This study traces the history and dark memories on Galang Island, as well as Indonesia's role in providing temporary protection for Vietnamese refugees as part of global humanitarian history. This research method uses qualitative with data collection techniques using observation, interviews with related people.